Karakterisasi Sifat Fisik Bioplastik Berbasis Pati Kulit Pisang Goroho dengan Penambahan ZnO - Devita Irawati Putri,; Jahja, Mohamad; Yunginger, Raghel; Latief, Muh. Fachrul; Ramadani, Andi Indra Wulan Sari (JFT: Jurnal Fisika dan Terapannya, 2025)
An effective way to address the plastic waste problem is by minimizing the use of non-biodegradable plastics. One approach is to develop biodegradable plastic packaging that is environmentally friendly. This research used Goroho banana peel starch, this type of banana is used because it has good potential with a starch content of 80.89%. In this research, variations in ZnO concentration of 1%, 2%, 3%, 4%, and 5% w/w were conducted. This research aims to determine the characteristics of physical properties of bioplastics with the addition of ZnO. This research uses a laboratory experimental method through several processes, namely goroho banana peel starch extraction and bioplastic manufacturing. The results indicated that varying concentrations of ZnO significantly influenced the physical and biodegradation properties of the bioplastic products. The physical properties of the bioplastics produced have met the Indonesian National Standard (SNI) for water uptake of 21.5% and biodegradation of 60 days. FTIR results show that the functional groups of bioplastics are identical to the constituent functional groups, namely starch, so that their properties resemble the properties of their constituents, which are easily degraded. The most optimum bioplastic is BPZ 2 with the addition of ZnO at 2% w/w, which produces water uptake of 1.859% and degradation time of 12 days.